Maqashid Sharia Analysis of the Decree on the Use of Zakat Funds for Disaster Management - Gustanto, Edo Segara; Asmuni, Asmuni (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This writing analyzes the decree regarding the use of zakat funds for disaster management using the Maqashid Sharia approach. Maqashid Sharia is a conceptual framework aimed at fulfilling the goals of Islamic law, such as hifzh al-mal (protection of wealth), hifzh an-nafs (protection of life), and hifzh ad-din (protection of religion). The analysis covers aspects of legality, utility, and the balance of zakat fund distribution in facing disaster situations. The results of this analysis are expected to provide a deeper insight into the relevance and effectiveness of the related decree in the context of disaster management while adhering to the principles of Maqashid Sharia. In writing this article, the author adopts the Maqashid Sharia perspective of Imam Asy-Syatibi. Asy-Syatibi is chosen because he is one of the great scholars who formulated the science of Maqashid asy-shari'ah and al-muwafaqat. Imam Syatibi's most significant work, al-muwafaqat, is a scholarly contribution to the field of usul fiqh and a comprehensive reform of Islamic scholarship. According to Syatibi, Allah revealed the Sharia (legal rules) solely to bring about benefits and prevent harm (jalbul mashalih wa dar'ul mafasid). In simpler terms, the legal rules prescribed by Allah are for the benefit of humanity. Certainly, Asy-Syatibi's Maqashid Sharia approach can be linked to the issuance of a decree on the use of zakat funds for disasters in a humanitarian context.